Analisis Optimasi Desain Jaringan FTTH Berbasis GPON Menggunakan Pemetaan Wilayah pada Area Rural Kerinci Bengkolan Dua, Jambi - Khoirul Yazid; Dikky Chandra; Yulindon Yulindon (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study examines the optimization of Fiber To The Home (FTTH) network design using the Gigabit Passive Optical Network (GPON) architecture through a geographic mapping approach between customer houses and Network Points (NP). The background of this research lies in the inefficiency of conventional FTTH design in rural areas where house distribution is irregular, often causing excessive cable usage and higher optical attenuation. The objective of this study is to compare a conventional design scenario, where NP placement follows the feeder route, with an optimized scenario that assigns each house to the nearest NP based on geographic proximity. A comparative design analysis method was applied using field observation data, estimated block dimensions, and visual network mapping. The findings indicate that the geographic mapping approach significantly reduces total cable length by 2,586 meters, primarily from shorter drop cables, resulting in a more organized cable layout and easier network maintenance. This optimization also implies lower material usage, reduced attenuation, and better network scalability. The results demonstrate that nearest-distance-based design provides a practical and efficient solution for FTTH deployment in rural environments with non-uniform house patterns.